2008
DOI: 10.1074/mcp.r800013-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

A Genecentric Human Protein Atlas for Expression Profiles Based on Antibodies

Abstract: An attractive path forward in proteomics is to experimentally annotate the human protein complement of the genome in a genecentric manner. Using antibodies, it might be possible to design protein-specific probes for a representative protein from every protein-coding gene and to subsequently use the antibodies for systematical analysis of cellular distribution and subcellular localization of proteins in normal and disease tissues. A new version (4.0) of the Human Protein Atlas has been developed in a genecentri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
468
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 581 publications
(496 citation statements)
references
References 32 publications
18
468
2
3
Order By: Relevance
“…Perhaps the largest assessment comes from work published by the Human Protein Atlas, a Swedish consortium that aims to generate antibodies for every protein in the human genome. It has looked at some 20,000 commercial antibodies so far and found that less than 50% can be used effectively to look at protein distribution in preserved slices of tissue 5 . This has led some scientists to claim that up to half of all commercially available antibodies are unreliable.…”
Section: Devastating Effectsmentioning
confidence: 99%
“…Perhaps the largest assessment comes from work published by the Human Protein Atlas, a Swedish consortium that aims to generate antibodies for every protein in the human genome. It has looked at some 20,000 commercial antibodies so far and found that less than 50% can be used effectively to look at protein distribution in preserved slices of tissue 5 . This has led some scientists to claim that up to half of all commercially available antibodies are unreliable.…”
Section: Devastating Effectsmentioning
confidence: 99%
“…Alarmingly, there are serious flaws in the reliability of antibodies, the most widely used class of protein-binding reagent 2,3 .…”
Section: Standardize Antibodies Used In Researchmentioning
confidence: 99%
“…In the lab, biologists have long used them to track proteins of interest because they bind to specific targets. But in a 2008 study 3 , fewer than half of around 6,000 routinely used commercial antibodies recognized only their specified targets, with some manufacturers producing consistently good antibodies, and others consistently poor ones.…”
Section: Standardize Antibodies Used In Researchmentioning
confidence: 99%
“…Current estimates suggest approximately 50 per cent of antibodies are either unreactive towards the purported epitope or cross-react with others (Berglund et al 2008). This problem is amplified by common chemical treatments on the collected tissues that are necessary for many immunohistochemical techniques.…”
Section: Current Limitations Of Viewing and "Quantifying" Neuroinflammentioning
confidence: 99%